Communication Processes and Professional Satisfaction in Golf Teachers in the Community of Madrid - Gismera Tierno, Eduardo; Paredes Serrano, Cristina (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
Business organisations in the golf sector aim to provide a high-quality service, whether operating independently, within sports clubs, or where the club itself employs instructors. This study focuses on the influence of communication processes on the instructor–company–client relationship and empirically explores the link between the effectiveness of organisational communication and professional satisfaction, as perceived by professionals, and its impact on organisational trajectory. Interviews were conducted at several golf clubs in the Community of Madrid during June and July 2024, and responses were analysed using a term analysis tool. The work contributes new knowledge and empirical evidence to academic literature and the growing golf sector in Spain, offering insights into current and future approaches to company–instructor relations. The primary conclusion highlights the need to implement efficient communication processes to enhance job satisfaction, even in companies where existing practices are considered adequate, as a key indicator for improved management.